Conditional survival after neoadjuvant chemoradiotherapy and surgery for oesophageal cancer. Issue 8 (3rd February 2020) - Hagens, E. R. C.; Feenstra, M. L.; Eshuis, W. J.; Hulshof, M. C. C. M.; van Laarhoven, H. W. M.; van Berge Henegouwen, M. I.; Gisbertz, S. S.
Abstract : Background: Conditional survival accounts for the time already survived after surgery and may be of additional informative value. The aim was to assess conditional survival in patients with oesophageal cancer and to create a nomogram predicting the conditional probability of survival after oesophagectomy. Methods: This retrospective study included consecutive patients with oesophageal cancer who received neoadjuvant chemoradiation followed by oesophagectomy between January 2004 and 2019. Conditional survival was defined as the probability of surviving y years after already surviving for x years. The formula used for conditional survival (CS) was: CS( x | y )  = S( x  +  y ) /S( x ), where S( x ) represents overall survival at x years. Cox proportional hazards models were used to evaluate predictors of overall survival. A nomogram was constructed to predict 5‐year survival directly after surgery and given survival for 1, 2, 3 and 4 years after surgery. Results: Some 660 patients were included. Median overall survival was 44·4 (95 per cent c.i. 37·0 to 51·8) months. The probability of achieving 5‐year overall survival after resection increased from 45 per cent directly after surgery to 54, 65, 79 and 88 per cent given 1, 2, 3 and 4 years already survived respectively. Cardiac co‐morbidity, cN category, ypT category, ypN category, chyle leakage and pulmonary complications were independent predictors of survival. The nomogram predicted 5‐year survival using these predictors and number of years already survived. Conclusion: The probability of achieving 5‐year overall survival after oesophagectomy for cancer increases with each additional year survived. The proposed nomogram predicts survival in patients after oesophagectomy, taking the years already survived into account. Abstract : Conditional survival accounts for the time already survived after surgery and may be of additional informative value. A nomogram was constructed that predicts 5‐year survival of patients with oesophageal cancer after neoadjuvant treatment followed by surgery, based on cardiac co‐morbidity, cN category, ypTN stage, chyle leakage and pulmonary complications, taking years already survived into account. Informative for patient and doctor Abstract : Antecedentes: La supervivencia condicional hace referencia al tiempo ya sobrevivido tras la cirugía y esta información puede tener un valor adicional. El objetivo fue evaluar la supervivencia condicional en pacientes con cáncer de esófago y crear un nomograma para predecir la probabilidad condicional de supervivencia tras una esofaguectomía. Métodos: Estudio retrospectivo incluyó pacientes consecutivos con cáncer de esófago que fueron tratados con quimiorradioterapia neoadyuvante seguida de cirugía, entre enero de 2004 a 2019, en el centro médico de la Universidad de Amsterdam (AMC) de los Países Bajos. La supervivencia condicional se definió como la probabilidad de sobrevivir y años tras haber ya sobrevivido ya durante x años. La formula utilizada fue: CS(x|y) =S(x+y) /S(x), con S(x) representando la supervivencia global a x años. Se utilizaron modelos de riesgo proporcional de Cox para evaluar los predictores de supervivencia global. Se construyó un nomograma para predecir la supervivencia a los 5 años directamente tras la cirugía y dar la supervivencias a 1‐, 2‐, 3‐ y 4 años después de la cirugía. Resultados: Se incluyeron 660 pacientes. La mediana de la supervivencia global fue de 44, 4 meses (i.c. del 95% 37, 0‐51, 8). La probabilidad de conseguir una supervivencia global a los 5 años tras la resección aumentó del 45% directamente después de la cirugía al 54%, 65%, 79% y 88% por cada año adicional sobrevivido. La comorbilidad cardiaca, estadio cN, estadio ypT, estadio ypN, quilotórax y complicaciones pulmonares fueron predictores independientes de supervivencia. El nomograma predijo la supervivencia a 5 años utilizando estos predictores y número de años ya sobrevividos. Conclusión: La probabilidad de alcanzar una supervivencia global a los 5 años tras una esofaguectomía por cáncer aumenta por cada año adicional sobrevivido. El nomograma propuesto predice la supervivencia en pacientes después de una esofaguectomía, teniendo en cuenta los años ya sobrevividos.